Biscuits of number theory - Benjamin, Arthur T. 1961- (Mathematical Assoc. of America, 2009)
An anthology of articles designed to supplement a first course in number theory.
Keywords: Arithmetic; Fermat's last theorem; Fibonacci numbers; Number theory; Zahlentheorie; Aufsatzsammlung